PENGARUH MOTIVASI KERJADAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN STARBUCKS DISTRIK 42 DI JAKARTA - Bagas Mardiansyah; Enny Savitri (Journal of Research and Publication Innovation, 2024)
The aimofthisre search istodetermine thei nfluence of work motivation andwork environment on the performance of Starbucks District 42 employees in Jakarta. The methoduse disquantitative. The sampling techniqueusedsaturated sampling, namely 80 respondents. Data analysis uses validitytests, reliabilitytests, classicalassumptiontests, regressionanalysis, correlationcoefficients, coefficients of determination and hypothesis testing. The results of thisresearch are that work motivation has a significant effect on employee performance with a coefficient of determination valueof 51.5% and the hypothesist estobtained t count> t tableor (9.094 > 1.991). The workenvironment has a significant effect on employee performance with a coefficient of determination value of 40.8% and the hypothesist estobtained t count> t tableor (7.338 > 1.991). Work motivation and work environment simultaneously have a significant effect on employee performance witht here gressionequation Y = 9.275 + 0.463X1 + 0.299X2. The coefficient of determination valueis 57.3% while the remaining 42.7% is influenced by other factors. Hypothesis testing obtained a calculated F value> F tableor (51.608 > 2.720).